Optimalisasi Komunikasi Pada Unit Pelayanan Publik dan Publikasi Balai Pelestarian Cagar Budaya Sulawesi Selatan Di Era Digital - Munawaroh, Munawaroh; Zelfia, Zelfia (UNIVERSITAS MUSLIM INDONESIA, 2022)
This study aims to describe the optimization of communication in Public Services and Publications in the Digital Era in the implementation of good services in the digital era by utilizing technology at the South Sulawesi Cultural Heritage Preservation Center. This study uses a qualitative descriptive method. The results showed that the optimization of public service communication and publications of the Cultural Conservation Preservation Center in the Digital Era went well, due to the establishment of good communication between employees, and jointly improving the quality of self and knowledge in the face of an increasingly developing technological era. Services carried out with the aim of making it easier for the public to access information related to cultural heritage, namely providing the website bpcbsulsel.id, youtube accounts, instagram, virtual reality, film documentaries, mobile cinemas and talk shows on tv have been able to be accessed by the public which can be seen by increasing requests for utilization. cultural heritage sites and the increasing number of people who come to visit the South Sulawesi Cultural Heritage Preservation Center located at Fort Rotterdam, so that people can easily access the information provided.